HLA-B may be more protective against HIV-1 than HLA-A because it resists negative regulatory factor (Nef) mediated down-regulation. - Rajapaksa, US; Li, D; Peng, Y; Mcmichael, A; Dong, T; Xu, X (2012)
Human leukocyte antigen HLA-B alleles have better protective activity against HIV-1 than HLA-A alleles, possibly due to differences in HLA-restricted HIV-1-specific CD8+ cytotoxic T lymphocyte (CTL) function, but the mechanism is unknown. HIV-1 negative regulatory factor (Nef) mediates down-regulation of surface expression of class I HLA (HLA-I) and may therefore impair immune recognition by CTL. Because of sequence differences in the cytoplasmic domains, HLA-A and -B are down-regulated by Nef but HLA-C and -E are not affected. However, the latter are expressed at low levels and are not of major importance in the CTL responses to HIV-1. Here, we compared the role of the cytoplasmic domains of HLA-A and -B in Nef-mediated escape from CTL. We found HLA-B cytoplasmic domains were more resistant to Nef-mediated down-regulation than HLA-A cytoplasmic domains and demonstrated that these differences affect CTL recognition of virus-infected cells in vitro. We propose that the relative resistance to Nef-mediated down-regulation by the cytoplasmic domains of HLA-B compared with HLA-A contributes to the better control of HIV-1 infection associated with HLA-B-restricted CTLs.